DIFFERENCES OLD PERINEAL WOUND HEALING POST HECTING WITH ANESTHESIA AND WITHOUT ANESTHESIA IN POSTPARTUM MOTHERS IN BPM "Y" AND BPM "G" LUBUK ALUNG 2015 - Septya, Angelia Rovina; Kustanto, Debby Ratno (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
Tailoring perineum is the effort to improve the function of the reproductive organs of women with rupture during childbirth. The use of anesthesia in suturing perineal laceration is dear mother's care. Practical experience in D-III of Midwifery, anesthetic administration before done throughout the midwife with the grounds for granting anesthesia can slow wound healing. This study aims to determine whether there are differences in wound healing post heating perineum between the mother given anesthesia before suturing the perineum with mothers who are not given anesthesia before suturing the perineum. This type of research is pre-experimentation, design research group intact comparison. research conducted on 1 October to 20 October 2015 in BPM "G" and BPM "Y" Lubuk Alung with a total sample of six people, the sampling technique accidental sampling. Data analysis was done by Independent T statistical test. The results showed long wound healing using anesthesia is 10 days while the healing of wounds that do not use anesthesia is 6 days. Bivariate analysis results can be concluded there is a difference in the rate of wound healing between the mother given anesthetic before action is taken by the mothers perineal suturing were not given anesthesia before action is taken perineal suturing with a P value of Value 0.013 (<0.05). Health workers must increase their skills and communication in case of normal delivery in order to rupture perineum reduced and teach patients how to wound care of perineal is good and right that wound healing is rapid and normal in hope of decreasing the risk of infection during childbirth.